The Popeye domain containing 2 (popdc2) gene in zebrafish is required for heart and skeletal muscle development - Kirchmaier, Bettina C. (2012)
The Popeye domain containing (Popdc) genes encode a family of transmembrane proteins with an evolutionary conserved Popeye domain. These genes are abundantly expressed in striated muscle tissue, however their function is not well understood. In this study we have investigated the role of the popdc2 gene in zebrafish. Popdc2 transcripts were detected in the embryonic myocardium and transiently in the craniofacial and tail musculature. Morpholino oligonucleotide-mediated knockdown of popdc2 resulted in aberrant development of skeletal muscle and heart. Muscle segments in the trunk were irregularly shaped and craniofacial muscles were severely reduced or even missing. In the heart, pericardial edema was prevalent in the morphants and heart chambers were elongated and looping was abnormal. These pathologies in muscle and heart were alleviated after reducing the morpholino concentration. However the heart still was abnormal displaying cardiac arrhythmia at later stages of development. Optical recordings of cardiac contractility revealed irregular ventricular contractions with a 2:1, or 3:1 atrial/ventricular conduction ratio, which caused a significant reduction in heart frequency. Recordings of calcium transients with high spatiotemporal resolution using a transgenic calcium indicator line (Tg(cmlc2:gCaMP)(s878)) and SPIM microscopy confirmed the presence of a severe arrhythmia phenotype. Our results identify popdc2 as a gene important for striated muscle differentiation and cardiac morphogenesis. In addition it is required for the development of the cardiac conduction system.